2021
DOI: 10.1111/petr.14025
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the 2020—2021 influenza season

Abstract: The COVID‐19 pandemic has altered health seeking behaviors and has increased attention to non‐pharmaceutical interventions that reduce the risk of transmission of respiratory viruses including SARS‐CoV‐2 and influenza. While the potential impact of the COVID‐19 pandemic on influenza is not fully known, in the Southern hemisphere influenza infection rates appear to be very low. Influenza vaccine efficacy for 2019–2020 season was comparable to prior season and influenza vaccine recommendations for pediatric immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Thus, many studies have shown that nonpharmaceutical interventions associated with reduced transmission of COVID-19 have also likely substantially reduced influenza [ 11 , 12 ]. Indeed, the 2019–2020 influenza season was marked by decreased influenza transmission during the COVID-19 pandemic [ 13 ]. Shenzhen is located in southern China; it has a typical subtropical monsoon climate, where influenza is mostly detected in autumn and winter [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many studies have shown that nonpharmaceutical interventions associated with reduced transmission of COVID-19 have also likely substantially reduced influenza [ 11 , 12 ]. Indeed, the 2019–2020 influenza season was marked by decreased influenza transmission during the COVID-19 pandemic [ 13 ]. Shenzhen is located in southern China; it has a typical subtropical monsoon climate, where influenza is mostly detected in autumn and winter [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of the COVID-19 pandemic on influenza is not fully known, but the reason for the observed decrease may be multifactorial. First, the COVID-19 pandemic has altered health seeking behaviors and has increased attention to nonpharmaceutical interventions that reduce the risk of transmission of influenza [ 13 ]. Other factors, such as virus competition, may have contributed as well.…”
Section: Discussionmentioning
confidence: 99%
“…First, the Shanghai government increased the scope of in uenza vaccination, especially for young children aged 3-6 in kindergartens in September 2020. Next, the COVID19 pandemic has changed health-seeking behavior and increased the focus on non-pharmacological interventions to decrease the risk of infection with the spread of in uenza [19]. Meanwhile, many viral-viral interactions may also affect the incidence of respiratory viral infections.…”
Section: Discussionmentioning
confidence: 99%